2017
DOI: 10.2527/tas2017.0014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chromium supplementation on physiology, feed intake, and insulin related metabolism in growing pigs subjected to heat stress

Abstract: Improving insulin sensitivity may reduce impacts of heat stress (HS) in pigs by facilitating heat dissipation. Chromium (Cr) has been reported to improve insulin sensitivity in pigs. Therefore, the aim of this experiment was to investigate whether Cr supplementation can mitigate HS in growing pigs. Thirty-six gilts were randomly assigned to 2 diets containing 0 (control) or 400 ppb Cr. After 14 d the supplemented pigs were allocated to either 8 d thermoneutral (20°C constant; TN) or cyclic HS (35°C, 0900 h to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 45 publications
3
21
0
1
Order By: Relevance
“…While HS did not influence fasting glucose or insulin concentrations, HS did reduce plasma NEFA concentrations, consistent with previous results from our laboratory [17]. Reduced lipid mobilisation during HS is a characteristic metabolic response, and is thought to contribute to increases in carcass adiposity and potential carcass downgrades in meat species [2,6,25].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…While HS did not influence fasting glucose or insulin concentrations, HS did reduce plasma NEFA concentrations, consistent with previous results from our laboratory [17]. Reduced lipid mobilisation during HS is a characteristic metabolic response, and is thought to contribute to increases in carcass adiposity and potential carcass downgrades in meat species [2,6,25].…”
Section: Discussionsupporting
confidence: 90%
“…At approximately 08:00 on the last day of the heat period, animals were removed from their rooms and a catheter introduced to the middle or lateral auricular (ear) vein, and advanced so that the catheter tip was situated between the external jugular vein and anterior vena cava [17,18]. To complete this procedure, animals were moved from their metabolism crates into an open space and were restrained in the standing position by using a snout rope and ears were disinfected with 70% ethanol antiseptic solution.…”
Section: Intravenous Glucose Tolerance Testmentioning
confidence: 99%
“…Pigs are particularly prone to HS due to thick layers of subcutaneous adipose tissue and lack of functional sweat glands [5]. Previous studies have shown that pigs reared in hyperthermal conditions typically had lower skeletal muscle weight, higher fat tissue mass and poorer meat quality [6,7], and those responses are associate with the alternation of several metabolic parameters [8,9]. Liver is a key metabolic organ that regulated the whole-body metabolism in animals and humans.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al . [ 7 ] also reported that the detrimental effect of heat stress can be reduced by chromium supplementation in pigs. Chromium supplementation increases the insulin activity and improves glucose utilization [ 8 ].…”
Section: Introductionmentioning
confidence: 99%